Validation of the GPAT – the Global Polypectomy Assessment Tool: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Smeets, Sander; Argenziano, Maria Eva; De Crem, Alexander C.; Desomer, Lobke; Anderson, John; Bhandari, Pradeep; Boškoski, Ivo; Bugajski, Marek; Bourke, Michael J.; Debels, Lynn; Heitman, Steven J.; Kashida, Hiroshi; Lee, Ralph R.T.; Lyutakov, Ivan; Rivero-Sánchez, Liseth; Schoonjans, Christophe; Thomas-Gibson, Siwan; Thorlacius, Henrik; Fuccio, Lorenzo; Tham, Tony C.; Bisschops, Raf; Tate, David J. (Endoscopy, 2025)
Background Colorectal polypectomy is operator dependent, with variable rates of complete resection. The currently available assessment tools do not provide specific competency-based evaluation of provider technique. We aimed to validate the Global Polypectomy Assessment Tool (GPAT), a novel competency assessment tool for colorectal polypectomy.Methods GPAT was derived from the ESGE Curriculum for Training in endoscopic mucosal resection in the colon. Members of the curriculum taskforce plus three invited trainees and three medical students (collectively: the assessors) anonymously assessed nine endoscopic-view only polypectomy videos. The primary end point was the correlation of the assessors’ GPAT scores with a consensus-derived reference GPAT score per video. Secondary end points were the assessors’ subjective impression versus their GPAT score and interobserver agreement among assessors’ GPAT scores. Results 171 GPAT assessments by 19 assessors (consultant gastroenterologists [n = 10], trainee gastroenterologists [n = 4], consultant surgeons [n = 2], and medical students [n = 3]) were analyzed. Reference GPAT scores did not differ significantly from those of the assessors (73.1 % [95 %CI 64.6 %–81.6 %] vs. 69.3 % [95 %CI 64.9 %–81.2 %]; P = 0.47). There was moderate IOA in GPAT scores among gastroenterologists (intraclass correlation coefficient [ICC], 0.52 [moderate]) but not among nongastroenterologists (ICC 0.32 [poor]). GPAT correlated with assessors’ subjective impression of polypectomy quality (correlation coefficient 0.98 [95 %CI 0.90–1.00]; P < 0.001). Overall assessors’ qualitative usability scoring of GPAT was positive.Conclusions GPAT allows standardized scoring of polypectomies, with moderate IOA among gastroenterologists and correlation with subjective impressions of polypectomy quality. GPAT could standardize assessment of trainee polypectomy competency offering structured feedback on performance.